Chemical composition and antibacterial activity of essential oil from fruit of Micromelum integerrimum (Buch.-Ham. ex DC.) Wight & Arn. ex M. Roem. - Kotoky, R.; Bordoloi, M.; Yadav, A.; Tamuli, K. J.; Saikia, S.; Dutta, P. P.; Saikia, S. P.
The essential oil extracted from fruit of Micromelum integrrimum were evaluated through gas chromatography and gas chromatography-mass spectroscopy. 52 compounds were identified from the fruit oil representing 99.98 per cent of the oil. The major components of the total fruit oil are monoterpene hydrocarbons (72.23 per cent), oxygenated monoterpenes (14.78 per cent)and sesquiterpene (11.54 per cent)which were predominated by terpinolene (32.21 per cent), ?-pinene (17.24 per cent), ?-pinene (17.24 per cent), and camphene (4.05 per cent). Moreover, other components that present in 1.45 per cent were aromatic compounds, fatty acid, etc. The essential oil exhibited broad spectrum antimicrobial activity which is concentration dependent and 100 ?L of the fruit oil showed the inhibition zones ranging from 7-16 mm. Fruit oil exhibited strong inhibition activity compared to standard anti-bacterial drug neomycin B (22 mm)against Bacillus subtilis MTCC 441 and Bacillus spizizenii ATCC 6633. This is the first hand report on the chemical profiles and promising anti-microbial activity of Micromelum integrrimum fruit essential oil towards Basillus Sp.
Keywords: MICROMELUM INTEGRRIMUM; ESSENTIAL OILS; CHEMICAL COMPOSITION; ANTI-MICROBIAL ACTIVITY